El pez arco iris y la ballena azul - Pfister, Marcus; Pereira, Delza (New York : Ediciones Norte-Sur, 1998)
When a big blue whale comes to live near their reef, there is a misunderstanding between him and Rainbow Fish and his friends that leaves everyone very unhappy and hungry.
Accelerated Reader
Keywords: Fishes -- Juvenile fiction; Whales -- Juvenile fiction; Fighting (Psychology) -- Juvenile fiction; Peces -- Novela juvenil; Ballenas -- Novela juvenil; Combatividad (Psicología) -- Novela juvenil